THE PLACE OF ADMINISTRATIVE LAW STANDARDS IN THE SYSTEM OF LEGAL BASES FOR ENSURING CONTROL AND SECURITY IN THE SPHERE OF BANKING ACTIVITIES IN UKRAINE (Bulletin of criminological association of Ukraine, 2024)
It is argued that the legal principles of ensuring control and security in the sphere of banking activity in Ukraine represent a set of normative and legal acts of different legal force, the norms of which are aimed at regulating social relations in the studied field of social life. It has been established that the system of legal foundations for ensuring control and security in the field of banking activity consists of a large number of regulatory legal acts of various branches. It has been proven that in the system of relevant principles, the key place is given to the norms of the administrative field of law, because it is with the help of the latter that the following are determined: the powers and competence of the subjects of state power, which implement activities in the sphere of banking regulation; the procedure for prosecution and the degree of legal responsibility for committing offenses in this area; imperative requirements and standards of conducting banking activities, in particular, in a special period; principles of information and technical support in the work of banks; administrative measures related to the prevention of money laundering (legalization) of criminally obtained income by banks and the like.
Keywords: legal principles; administrative and legal regulation; control; security; banking activity